CdS Loaded an Iranian Clinoptilolite as a Heterogeneous Catalyst in Photodegradation of p-Aminophenol - Alireza Nezamzadeh-Ejhieh; Khodarahm Shirvani (Journal of Chemistry)
Natural clinoptilolite, zeolite  CdS-incorporated  was prepared by ion exchange and precipitation procedures and it was characterized by FT-IR, XRD, and thermal methods. The prepared composite was used as a catalyst in the photodegradation process of p-aminophenol in aqueous solution under UV irradiation. The effect of some key operating parameters such as catalyst dosage, temperature, the initial concentration of the pollutant, and initial pH of the solutions on the degradation process of the pollutant was studied. The primary objective was to determine the optimal conditions for each of the parameters. UV-vis spectrophotometric measurements were performed for the determination of degradation and mineralization extents. The optimal operation parameters were found as follows: pH 5, 17.5 mg·L−1 of catalyst loading, and 10 ppm of dye concentration. The CdS particles out of zeolite framework do not show significant degradation efficiency. The degradation process obeyed first-order kinetics.